Sharia-Compliant Payment Preferences in TikTok Shop E-Commerce: Consumer Behavior in Silaut District - Oktavia Berliana Veronika; Niken Miranda Oktavia (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
This study explores consumer payment preferences on TikTok Shop. It evaluates the extent to which these payment methods align with sharia-compliant principles, focusing on user experiences in Silaut District. The research aims to identify the dominant payment choices, understand the factors influencing these choices, and assess their compliance with Islamic economic ethics. Data were collected through in-depth interviews with active TikTok Shop users, allowing the researchers to capture personal experiences, financial capabilities, and perceptions regarding trust and convenience in online transactions. The findings reveal that Cash on Delivery is the most preferred payment method due to its flexibility, ease of preparation, and the sense of security it provides, especially for users with irregular income or limited digital wallet access. Meanwhile, transfer payments using OVO and DANA are used when required by sellers or when users have a sufficient balance. Both payment methods fulfill sharia principles of mutual consent, fairness, and transparency, and are free from elements of riba, gharar, and maysir. The study concludes that TikTok Shop accommodates rural consumer needs while maintaining sharia-compliant transaction standards, offering valuable insights into digital commerce behavior in Muslim-majority rural communities.